Qualidade das informações em sistemas de gestão empresarial para atender ao convênio ICMS 57/95 : estudo de caso em empresa de distribuição de GLP - Santos, Luiz Carlos dos (2003)
This research is based on a case study performed in a liquefied petroleum gas (LPG) multinational retailing company, and aims to describe the experience and consequences of its relationship with the Government, as a result of the deployment of an Enterprise Management System, as defined by the legislation accessory obligations, specifically the ICMS 57/95 covenant. The system s deployment process has been mapped, as well as its performance and the gap between the real and the ideal, so as to meet the accessory obligations regulated by the ICMS 57/95 covenant. This research also highlights the importance of the information in the organization, warning to quality issue of data and information that are processed and generated by the Enterprise Management Systems. The aim of the research is the development of a critical analysis of a contingence and the answer by the company, by means of an information system with quality.